2022
DOI: 10.18559/ebr.2022.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Institutional investors and real earnings management: A meta-analysis

Abstract: The aim of the article is to examine the influence of institutional investor ownership on real earnings’ management (REM) practices through a meta-regression analysis (MRA) based on a sample of 225 estimations from 19 articles. Some of the available research suggests a mitigating role for institutional investors who can serve as external monitors and thus reduce earnings’ management activities which could have a negative impact on the company’s value. The results obtained from the basic model confirmed neither… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The result, however, might be of interest to legislators, as the positive relationship between family ownership and REM means that this type of ownership does not discourage companies from REM, and legislators should not expect it to do so. In another study, performed by Kabaciński et al (2022), the authors found that institutional investors in general are not significantly related to REM, but conditional dependence exists. Corporate policymakers and investors should be aware that both types of ownershipfamily and institutional -do not constrain REM practices, and they should adjust their expectations accordingly.…”
Section: Discussionmentioning
confidence: 93%
“…The result, however, might be of interest to legislators, as the positive relationship between family ownership and REM means that this type of ownership does not discourage companies from REM, and legislators should not expect it to do so. In another study, performed by Kabaciński et al (2022), the authors found that institutional investors in general are not significantly related to REM, but conditional dependence exists. Corporate policymakers and investors should be aware that both types of ownershipfamily and institutional -do not constrain REM practices, and they should adjust their expectations accordingly.…”
Section: Discussionmentioning
confidence: 93%
“…Earnings management relates to many areas of corporate finance management, including window-dressing around equity or debt issues, financial distress, or its many interconnections with corporate governance (Campa, 2019;Friedlan, 1994;Grabiński & Wójtowicz, 2022;Kabaciński et al, 2022;Lizińska & Czapiewski, 2023;Piosik & Genge, 2020). One of these is cash holdings management, which is an important part of corporate financial strategy.…”
Section: Introductionmentioning
confidence: 99%